A COMPARATIVE STUDY OF KINDS, FUNCTION, AND POSITION OF QUESTION WORDS IN ENGLISH AND BAHASA BATAK TOBA - Sahlan Tampubolon (Jurnal Suluh Pendidikan, 2020)
Toba in terms of kinds, functions and positions. The data were taken from the Holy Bible written on Matthew’s book Chapter 1-28 with English and Bahasa Batak Toba Version. The question words found there were contrasted to see the similarities and differences. The research findings showed that English has nine types of question words, they are: Who, This study is about the similarities and differences of question words in English and Bahasa Batak Whom, What, Where, When, Why, How, Which, and Whose. While in Bahasa Batak Toba, there are eleven types of question words, they are Aha, Ise, Boha, Dia, Andigan, Nandigan, Piga, Sadia, Boasa, Mahua, and Marhua. In terms of functions, Both English and BahasaBatak Toba’s question words are used to ask for person, place, time, thing, reason, manner, activity, and possession. The position of English question words occurred at the beginning or in the middle of an interrogative sentence, while Bahasa Batak Toba’s question words take place at the beginning,in the middle, and at the end of interrogative sentences.